Farmer’s Household Economy working on conflict areas in The Meru Betiri National Park - Purwanto Purwanto; Sigit Andy Cahyono; Casimerus Yudi Lastiantoro; Nana Haryanti (School of Postgraduate Studies, Diponegoro Univer, 2017)
Forest land conflict in Meru Betiri National Park is considered as one of the kind of land conflicts in the forest conservation of Indonesia. The conflict has been taking place between MBNP and the people who live around the forest area (Wonoasri, Sanenrejo, Andongrejo, Curahnongko, and Kandangan) since 1998. The purpose of this research is to know the history of land conflict in Meru Betiri National Park and the impact of land rehabilitation on farmer's income This study was conducted in 2016. Qualitative research was conducted to obtain the historical information of MBNP land conflict and the survey was done to collect data of contribution of cultivation activities in the rehabilitation land (conflict area) on the income of farmers. The forest land conflict took place due to the vacant authority of the central government in 1998 which spread to the local government, so the government is not able to control the illegal harvesting of forest resources and forest area encroachment conducted by the public. In 1999, the local politicians of Indonesian Democratic Party proposed to the Ministry of Forestry in order the conflicted area of MBNP can be cultivated by the people around the area. In 2000, The Forestry Minister issued regulations stated that the assigned land is a rehabilitation zone. The rehabilitation zone must be planted with Multiple Purposes Tree Species (MPTS) and seasonal crops by using agroforestry system. The purpose of MPTS planting is for reforestation and the seasonal crops plantation is addressed for increasing the income of the farmers. After implementing the program for 15 years, the income generated from the rehabilitation land only Rp. 3,517,100,- (US 1 = Rp. 13,400,-) per year or 14,49% of the total income of the farmers. The income from the rehabilitation land contributed as the third source of incomes b esides the non land-based sources of income and the income from migrated remittance.